Analisis Ekonomi dan Kelayakan Pemanfaatan Gedung Terminal Tipe A Gambut Barakat Menjadi Sarana Belajar Kampus UNISKA - Vira Monica Puteri; Ika Chandriyanti (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine the financial feasibility of the Terminal Gambut Barakat before the BMN lease collaboration with UNISKA, identify the level of sensitivity of the Terminals cash flow after the partnership, and find out the social benefits of this collaboration when viewed from the perspective of UNISKA and the people of Banjar Regency. This study uses descriptive qualitative methods with data analysis techniques, namely financial feasibility analysis and sensitivity analysis.The result of this study indicates that before the cash flow cooperation, Terminal Gambut Barakat was not financially feasible. After the lease agreement was put, it was also still not financially feasible, even though the opening of the UNISKA campus at the Terminal Gambut Barakat was categorized as financially unfeasible. Still, this collaboration provided many social benefits for the people of Banjar Regency and its surroundings.